Associations between gestational weight gain and preterm birth in Puerto Rico - Stephanie M. Eick; Michael Welton; Mechelle D. Claridy; Skarlet G. Velasquez; Nicholas Mallis; José F. Cordero (BMC, 2020)
Abstract Background Preterm birth (PTB; gestational age < 37 weeks) is the leading cause of infant morbidity and mortality worldwide. Low and excessive gestational weight gain (GWG) have been previously cited as risk factors for PTB, however the magnitude of association varies across populations. No studies have examined low and excessive GWG as modifiable risk factors for PTB in Puerto Rico, an area with inexplicably high PTB rates. Methods To examine the relationship between GWG and PTB, we conducted a retrospective analysis using birth certificate data files from the Puerto Rico Department of Health from 2005 to 2012. GWG was standardized to a 40-week gestational duration and was categorized into low, adequate, or excessive for each category of pre-pregnancy body mass index using American College of Obstetricians and Gynecologists guidelines. Logistic regression was used to determine the crude and adjusted odds ratios (OR) and 95% confidence intervals (CI) for the association between GWG and PTB. Results There were 320,695 births included in this analysis; 40.6% with high GWG and 27.3% with low GWG. A greater percentage of women with low GWG were less than 20 years of age, had less than a high school education, and were underweight compared to women with adequate and excessive GWG. Women with low compared to adequate GWG had increased odds of PTB (OR = 1.34, 95% CI = 1.30-1.37). However, excessive compared to adequate GWG was not associated with PTB (OR = 0.99, 95% CI = 0.97-1.02). Conclusions Among women in Puerto Rico, low GWG was associated with increased odds of PTB. With the exception of obesity, these associations persisted within all strata of pre-pregnancy body mass index, highlighting the importance of maintaining a healthy weight during pregnancy. Future research should examine other factors that may contribute to GWG, such as dietary nutrients, and explore pathways through which GWG may be contributing to PTB.